OPTIMALISASI CAHAYA SIANG HARI DI RUANG RAWAT INAP DI .D.I. YOGYAKARTA - , Utdin Furqon Amali; , Ir. Jatmika Adi Suryabrata, MSc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the effort to support the thrift energy issue, hence require to existence of the thrift available of exploiting fossil fuel energy. Our state resides in the equator, which always get daylight every day as long as years. Availability of the daylight in the world is not limited. Exploiting daylight energy as source lighting in the day therefore will be able to economized usage of fossil fuel to process to yield illumination energy. For that require to optimize daylight as lighting natural in wards. Wards have exploit optimum the daylight as the illumination if patient prefer wards illumination, have the illumination appearance which can attention dweller, have highest level of distribution illumination or uniformity illumination, and don't required electric illumination and only use daylight as illumination at the day. The assorted factors of which influence of the illumination at the day, sun shading factor is the most factor which determine in distribute the daylight into room. Sun shading become most factor determine because sun hading not only chase direct daylight able to resulted glare also can reflected light from exterior to interior. Ability reflects this will be able to instructed illumination to the place which dark, to area activity and to the other place which wish. So that space can have uniformity illumination, which more interesting and take a fancy to the patient.